Space time block coding to enable MIMO-OFDM RADCOM systems - Costa, Samuel Dias (2021)
The available bandwidth in the radio frequency spectrum is decreasing due to the growing number of applications and users. Therefore, in order to ensure a sustainable evolution in this area it is crucial to develop strategies to optimize the spectrum usage. Joining RADAR and communication functionalities in a single terminal represents exactly this same strategy. As such, the two functionalities, which usually compete for the same radio resources, can coexist through a cooperative relation in which they can thrive and cease to introduce interferences in between them. In this dissertation, the integration of both systems is achieved through the use of OFDM as the common waveform. Through the space time/frequency block codes, namely the Tarokh coding it is possible to introduce spatial diversity and orthogonality to the system, therefore increasing the system’s robustness and allowing to use the virtual antenna concept, which enables improved RADAR resolution and detection. In order to evaluate the system’s performance, a simulation platform was developed. In these simulations we start by firstly considering RADAR detection for single and multiple antenna systems and then integrate the radar and communication functionalities. We have verified the good performance levels of the proposed system, which thanks to its low complexity can be an interesting RadCom approach for future wireless systems.